Family Support as a Factor in Cultural Adjustment - Lee , Pei-Chen (Chiu-Yi/Joy) (Journal of Law and Governance, 2007)
Following the growing worldwide competition and internationalisation of globe markets, international expatriates’ assignments are become more and more essential to successful worldwide development for many multinational corporations. Therefore, expatriates can become an important human resource to international enterprises or multinational operations. Especially, investigating the influential factors as family support of expatriate adjustment is significant for several reasons. Firstly, failure of expatriate adjustment may cause premature return from overseas assignments, which may be very costly financially for international enterprises. Secondly, failure to accomplish the plan of the assignment is as harmful to the expatriate as it is to the parent and host companies. Inability of an expatriate to complete the assignment is likely to damage his or her self-esteem, and self-confidence, and cause a loss of prestige among co-workers. Thirdly, an unsuccessful period of expatriation is likely to decrease both the subsequent commitment to the parent company. Therefore, to facilitate business expatriates adjustment to an overseas environment and to enable them to work effectively, Multinational Corporations (MNCs) need to recognise the expatriates’ family support factor to affect cross-cultural adjustment. The main purpose of this study involves utilising previous researcher Lee’s (2002) questionnaire to investigate the relationship between the family support and cross-cultural adjustment of Taiwanese Banks’ expatriates assigned to America, and this study employed same questionnaire to examine the relationship between the family and cross-cultural adjustment of Taiwanese expatriates in several different industries assigned to Mainland China. Also, the empirical outcomes were compared between Taiwanese expatriates located in Mainland China and United States. In examining the significant degree of Taiwanese expatriates assigned to Mainland China, the instrument was a questionnaire survey conducted to this study. The variables of interest were measured using items Likert-type questions, and those items are divided into seven categories. Data collected from 353 participants who have experience of a posting to Mainland China for international assignments. Multiple regression and correlation were employed to analyse data. The statistical results of this study were compared Lee’s (2002) research that associated with Taiwanese banking expatriates in United States. Both studies indicated that the expatriates’ family support factor to affect cross-cultural adjustment without doubt. This article concludes with suggestions for both international enterprises or MNCs and individual expatriate who operate overseas journey in their normal path of business.